Risk and all-cause mortality of high low-density lipoprotein cholesterol-albumin ratio level in stable coronary artery disease patients following percutaneous coronary intervention - Huang, Qianyin; Xia, Yunfeng; Zhang, Chenzhu; Lv, Minghua; Liang, Qiongyin; Zeng, Zixuan; Huang, Kaixin; Long, Yuxuan; Shi, Xiaoyan; Zhuo, Jingwen; Zhou, Erlin; Xing, Kaijun; et al. (Frontiers in Endocrinology, 2026)
BackgroundBoth low-density lipoprotein cholesterol (LDL-C) and albumin are well-established predictors of adverse outcomes in patients with stable coronary artery disease (CAD) who have undergone percutaneous coronary intervention (PCI). However, the risk and all-cause mortality (ACM) of the LDL-C-albumin ratio (LAR)—a composite index integrating these two parameters—remains unclear.MethodsThis study enrolled 198 consecutive patients with newly diagnosed stable CAD who underwent PCI at Shinonoi General Hospital between 2014 and 2017. The primary aim was to assess the risks related to high LAR levels and the association between LAR and ACM in this population.ResultsThe association between the LAR and ACM was evaluated through multiple methods. Analyzed as a continuous variable, each 1 mg/g increase in LAR conferred a 6% higher adjusted risk of ACM (Hazard Ratio [HR] 1.06, 95% Confidence Interval [95% CI] 1.00–1.12, P = 0.035). When categorized into quartiles (Q1-Q4) based on LAR level, the highest LAR quartile (Q4) shows a statistically significant 3.72–4.01-fold increase in ACM risk (vs. Q1) after covariate adjustment, the risk is not linear across all groups but is concentrated in the top 25% of patients with the highest LAR values. This finding was reinforced by an inverse probability of treatment weighting (IPTW) model, which demonstrated that patients with a high LAR (≥ 32.5 mg/g) had a 3.16-fold greater risk of ACM than those with a low LAR (95% CI 1.25–7.97, P = 0.028). Four-year Kaplan-Meier analysis confirmed that the high LAR group had a significantly lower adjusted survival probability (P = 0.017), with adjustments made for the same variables as those included in the IPTW analysis. In a separate analysis, LAR ≥ 32.5 mg/g is driven by elevated levels of atherogenic lipids (LDL-C, TC) and reduced serum albumin. Notably, the protective effect of male sex on high LAR-related risk requires further investigation.ConclusionsHigh level LAR is associated with ACM in stable CAD patients following PCI, with a level above 32.5 mg/g distinguishing a high-risk subgroup that warrants closer clinical monitoring due to a significantly elevated risk of adverse outcomes.